Barrier height determination of Au/Oxidized GaAs/n-GaAs using ballistic electron emission spectroscopy - Bosman, Michel (2013)
Ballisticelectron emission spectroscopy (BEES) was used to determine the electron barrier height at the interface of Au and an oxidizedGaAs film. Two thresholds were observed in the spectra. In a two-step procedure, we identified the first threshold at ∼1.4 eV, which we show arose from electron-hole pairs excited by photons emitted during scanning tunneling microscopy(STM), and the second threshold at ∼3.55 eV, which is attributed to the Au/oxidized-GaAs barrier. Our results demonstrate that the two-threshold behavior observed in BEES studies on metal/oxide samples is amenable to a physical model comprising of STMphotocurrent and a metal/oxide interface barrier.